Digital Content Development in the Kerala University Library: a Case Study - Beena, S. (Journal of Information and Knowledge, 2013)
The study focuses on the attempts made for the preservation of the resources relating to the history, science, art, culture, heritage, language, literature, economy and politics of the Kerala state. The paper emphasizes the need for digitization, the policy and criteria adopted for selecting the documents for digitization, the digitization process, and the digital preservation methods carried out by the Kerala University Library. The study attempts an analysis of the digitized documents. The need for coordinating the digitization efforts of various universities and institutions is also stressed in the paper.